2019
DOI: 10.21608/zumj.1999.25525
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Indices of Organophosphates Pesticides Among Agricultural Workers at Mit-Ghamr District, Egypt

Abstract: Background: Organophosphates pesticides (OPs) exert their toxicity on the body through inhibition of Cholinesterase Enzyme (ChE) in the nerve and muscle tissues. Inhibition of cholinesterase itself cannot account for the wide range of disorders that have been reported following OPs exposure as oxidative stress has been implicated as one of the mechanisms for the adverse health effects of OPs exposure. Aim of the study: To study oxidative stress among agricultural workers through assessment of blood level of Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Several reports recorded increased MDA hepatic levels in fipronil and dimethoate treated rats [85,88]. In addition, Elshamy, et al [76] reported a higher blood MDA level among agricultural workers compared to the non-exposed group following OPs exposure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several reports recorded increased MDA hepatic levels in fipronil and dimethoate treated rats [85,88]. In addition, Elshamy, et al [76] reported a higher blood MDA level among agricultural workers compared to the non-exposed group following OPs exposure.…”
Section: Discussionmentioning
confidence: 96%
“…Also, Yan, et al [16] concluded that MX induced oxidative stress in Zebra fish livers which confirmed by the increased SOD, CAT, and GPx activities. A study of oxidative stress among 48 agricultural workers exposed to OPs [76] demonstrated that the exposed group's blood SOD levels were considerably lower than the non-exposed group's. According to, Hernández et al, oxidative stress caused by pesticide exposure might cause SOD activity to be inhibited, resulting in superoxide radical buildup [77].…”
Section: Discussionmentioning
confidence: 99%